Dairy Business Analysis Project: 2008 Financial Summary - Albert De Vries; Mary Sowerby; Lane Ely; Russ Giesy (EDIS)
AN249, a 17-page illustrated report by A. De Vries, M. Sowerby, L. Ely, and R. Giesy, summarizes the financial performance of 14 dairy farms that participated in a 2008 survey. It is intended for general use by dairy farmers, the allied industry, government, and educational professionals. Published by the UF Department of Animal Science, August 2010.